La niña proletaria - Cartabia, Sabrina A. (2011)
The current paper aims to draw a parallel between Osvaldo Lamborghini?s\nshort story ?El niño proletario?, which, as the author suggests, introduces the reader to\nthe class struggle and the proletarian men and women?s subjection, and the subjugation\nsuffered by women, particularly through sexual violence. This way, the author\nasks herself if the power held by certain classes, does not also have an influence over\nwomen?s subjugation. Moreover, the essay also analyses how sexual violence works\nas a tool that constitutes the foundation of the inequality, the subjugation and the degradation\nof women, as well as an instrument of oppression of other vulnerable groups,\nsuch as children